A Comparison of Treatment Outcomes for Diabetes Between Telemedicine and Face-to-Face Interaction Modality in Primary Care Setting - Manosaksaree, Teerapol (Ramathibodi Medical Journal, 2025)
Background: Diabetes is a chronic disease and a significant global health issue. Currently, there are various treatment methods available, and telemedicine has become one of the widely used approaches today. However, there is still a lack of studies on its effectiveness, and patients remain concerned about the outcomes of their treatments. Objective: To compare treatment outcomes for diabetic patients between telemedicine and face-to-face interaction modalities. Methods: This study was a quasi-experimental design to compare 2 service delivery models between telemedicine and face-to-face modalities. Participants in both groups were followed for 6 to 9 months. Descriptive statistics were used for demographic data analysis and inferential statistics were applied to compare treatment outcomes. Results: Participants consisted of diabetic patients receiving treatment at 5 primary care unit, 77 participants were enrolled in the study, with 40 in the experimental group and 37 in the control group. The results showed that both groups demonstrated reductions in hemoglobin A1c (HbA1c), systolic and diastolic blood pressure , and low-density lipoprotein cholesterol (LDL-C) levels, with no significant differences between the groups (P > .05). Most participants reported similar levels of treatment satisfaction; however, those in the telemedicine group exhibited significantly lower confidence in the modality’s ability to prevent future diabetes-related complications (P < .05). Conclusions: The treatment outcomes of diabetic patients using telemedicine were comparable to those achieved through face-to-face interaction, with no significant differences in overall patient satisfaction between the 2 modalities.